2016
DOI: 10.7203/relieve.22.2.6832
|View full text |Cite
|
Sign up to set email alerts
|

Diversidad lingüístico-cultural e interculturalismo en la escuela andaluza: un análisis de políticas educativas

Abstract: Olmos-Alcaraz, Antonia (2016). Diversidad lingüístico-cultural e interculturalismo en la escuela andaluza: Un análisis de políticas educativas. RELIEVE, 22(2) , art. 7. doi: http://dx.doi.org/10.7203/relieve.22.2.6832 Autor de contacto / Corresponding authorOlmos Alcaraz, Antonia. AbstractThis paper is based on some research projects about immigration and education in Spain where I have been working on. The objectives of this work are: 1). To show the linguistic diversity of the students at Andalusian school… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 7 publications
0
5
0
3
Order By: Relevance
“…Six articles were found that applied the second intersectional approach: Brandão and Hill (2014); Dieltiens et al (2009); Olmos Alcaraz (2016); Balsera (2015); Song (2016); and Torres Corona (2014). The second practice of intersectionality is described as methodologically more complicated than that of the first.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Six articles were found that applied the second intersectional approach: Brandão and Hill (2014); Dieltiens et al (2009); Olmos Alcaraz (2016); Balsera (2015); Song (2016); and Torres Corona (2014). The second practice of intersectionality is described as methodologically more complicated than that of the first.…”
Section: Resultsmentioning
confidence: 99%
“…Her study focuses on South African townships, specifically. Balsera (2015) and Olmos Alcaraz (2016) confront the relationships of the colonized and the colonizer. Both examine the case of Ecuadorians who have moved to Spain.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…La preocupación por la multiculturalidad en las escuelas ha llevado a que diversos autores planteen los retos que conlleva educar en contextos educativos multiculturales (Zabalza, 1992;De Miguel, 1992;Bartolomé, 1999;Buendía, González, Pozo y Sánchez, 2004;Pérez Tapias, 2010;Arroyo, 2013;Banks, 2014;Verdeja, 2015;Olmos-Alcaraz, 2016).…”
Section: Introductionunclassified